Determination of Some Aromatic Hydrocarbon in Water of Tigris River near Al-Dora refinery - S. Hameed, Mohammed; S. Al-Zubaidi, Fawzi; S. Abdul Wahab, Ahmed (Iraqi Journal of Science, 2026)
This study aims to assess the concentrations of some Poly AromaticHydrocarbons in water, in order to monitor effectively and provide possiblerecommendations to improve the water quality in the aquatic ecosystem of TigrisRiver near Al-Dora refinery. Distribution and concentration of the sixteen polycyclicaromatic hydrocarbons (PAHs) were studied in surface water. Solid-phase extractionwas used for water samples, and then analyzed by HPLC. Results showed that thehighest and the most dominant (PAH) was ancephthlnene (3-ring PAH), withconcentration of (40.33 ng/l), while the lowest concentration was for Indeno (1, 2, 3-cd) pyrene (5-ring PAH), with (0.33 ng/l). The highest and the lowest meanconcentrations of PAHs were observed in autumn and summer, respectively. Ratiosof specific PAH compound including Phenantharene/Anthracene andFluoranthene/Pyrene were calculated to evaluate the possible sources of PAHscontamination. These ratios reflect a petrogenic origin of PAHs for water samples inDecember 2012, February 2013, April 2013 and October 2013, while in June 2013and August 2013 attributed to pyrolytic origins.